(untitled) (Journal of Forest and Livelihood, 2003)
This paper outlines the policy context and resource base for community forestry in Nepal. Drawing on a study of 11 Forest User Groups (FUGs) in the Middle hills region, the paper examines the process of FUG formation and post-formation support. The implementation process of community forestry demands rapid institutional change at Department of Forests (DoF) and village level, and changes in working relationships between these levels. The DoF’s main responsibilities in the Middle hills are changing from the traditional role of forest policing and protection, and moving towards FUG facilitation. However, the limited capacity of the DoF has become the key constraint to implementation of community forestry, and finding a solution may involve re-organizing the DoF support role. As new priorities emerge in FUGs (relating to community development for instance) involving multiple support agencies is becoming increasingly necessary.